(untitled) (Entrepreneurship Journal for Finance and Business, 2026)
Debt structure is a crucial focal point in banking sector performance, as the distribution of debt between short-term and long-term affects financial risks and the market value of banks. Within the Iraqi economic environment undergoing structural transformations, analysing this impact emerges as a strategic tool to enhance banking stability and attract investments. This study provides an in-depth analytical perspective on the impact of debt structure dimensions (short-term, long-term, and total) on the performance of Iraqi commercial banks, based on comprehensive field data and advanced statistical models, to offer actionable recommendations. This study aimed to analyse the impact of debt structure dimensions (short-term debt, long-term debt, and total debt) on the market value of Iraqi commercial banks. The study adopted the descriptive-analytical approach. The study population comprised (366) individuals from top, middle, and executive management levels, utilizing a comprehensive survey method. A set of statistical tools was employed, including (percentages, frequencies, arithmetic means, standard deviations, factor loadings, and impact analysis), relying on the (SmartPLS.4) program for structural equation modelling. The results revealed a high level of the overall performance indicator for both debt structure and market value. Furthermore, they demonstrated a statistically significant impact of all debt structure dimensions on the market value of the banking sector under study. In light of the findings, the study recommended developing programs to issue medium/long-term bonds in partnership with the Central Bank of Iraq (CBI), allocating at least 20% of the credit portfolio to this type of financing to support infrastructure projects with stable returns.